Laparoskopik Kolesistektomi Uygulanan Hastaların Taburculuk Öncesi Bilgi Gereksinimlerinin Belirlenmesi. - ZENGİN ÇAKIR, Hasret Kübra; DAL YILMAZ, Ümran (Turkiye Klinikleri Journal of Nursing Sciences, 2018)
Objective: The study was conducted to determine the information needs of the patients who underwent laparoscopic cholecystectomy before discharge and the roles of nurses in discharge training. Material and Methods: The study was carried out descriptively and cross-sectional. The sample of the research was composed between 15 December 2014-31 May 2015 in a state hospital, department of surgery, 78 patients undergoing laparoscopic cholecystectomy. As a data collection tool, questionnaire prepared by researcher by searching relevant literature has been used. The data were collected by the investigator face-to-face with the patients. For analysis of the data, SPSS (Statistical Package for the Social Sciences) 20.0 package program was used. Results: According to the results obtained from the study, it was determined that 28.2% of the patients were not informed about the operation in the preoperative period and 83.3% of the patients related to the emergency cases that should be referred to the doctor after discharge were not informed. With respect to home care of patients; 85.9% of patients were informed about wound care, 92.2% were about drugs, 78.2% were about nutrition, and 30.7% were informed about activities. It was determined that 94.6% of the patients informed by the physician were informed before the preoperative period. None of the patients were given discharge information in writing while being discharged from the hospital and 82.0% of the patients stated that they wanted a training booklet. Conclusion: It has been concluded that nurses do not take an active role in the discharge education process of the patients. It may be advisable to conduct planned discharge training in accordance with the individual characteristics of the patients and their learning needs and to prepare a patient education booklet.